ANALISIS NILAI MORAL PADA TOKOH DALAM CERPEN “KEADILAN” KARYA PUTU WIJAYA DENGAN MENGGUNAKAN TEORI SIGMUND FREUD - Irawati, Rani; Milah, Nuhbatul; Sahmini, Mimin (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the many moral values contained in the short stories circulating widely in Indonesia, one of which is justice short stories by Putu Wijaya. The short story has moral values, and this research focuses on the moral values contained in the short story. Therefore, this study aims to determine the moral value of the short story by using a qualitative descriptive method that is the depiction of the characteristics of each character to be analyzed based on the id, ego, and super ego. The results of this study are acts of injustice felt by the main character in the story. Judging from the behavior of the second character who is angry, emotional and chaotic without rules, as well as the third character that does not know the value of morality, do not know thank you. Both of these characters are analyzed with the three aspects of producing moral values of bad deeds that are not exemplary by reading good deeds can be seen from the behavior of the first character who has the characteristics of good, patient and able to control emotions. Therefore, analysis through Sigmund Freud's theory can be known moral values contained in the short story of justice that has good moral values and not good, it can be seen from the dialogue of each character.